Family Socioeconomic Status and Adolescent School Satisfaction: Does Schoolwork Support Affect This Association? - Horanicova, Simona; Husarova, Daniela; Madarasova Geckova, Andrea; de Winter, Andrea F.; Reijneveld, Sijmen A. (Frontiers in Psychology, 2022)
Background The aim of this study is to explore the association of family socioeconomic status (SES) and internal and external schoolwork support with adolescents’ school satisfaction and whether schoolwork support modifies these associations. Methods Data come from the cross-sectional Health Behavior in School-aged Children study collected in 2018 from Slovak 15-year-olds (N = 1127; 52.7% boys). SES was measured by Family Affluence Scale (low; middle; high). School satisfaction was measured via school engagement and attitudes toward education. Schoolwork support was measured regarding two groups of sources inside and outside the family, separately. Logistic regression models were used to explore the associations of SES and schoolwork support with school satisfaction as well as the moderating effect of schoolwork support. Results Adolescents with low SES were more likely to feel indifferent toward school and education (odds ratios/95%-confidence interval: 1.77/1.26–2.49), and similarly, adolescents who did not have schoolwork support inside or outside the family (1.38/1.02–1.87, and 1.50/1.01–2.22, respectively). Schoolwork support moderated the associations of SES with school satisfaction. Adolescents with low and middle SES without support inside or outside the family were more likely to feel indifferent than satisfied (2.72/1.21–6.10; 3.00/1.27–7.06; and 2.86/1.05–7.80; 6.04/1.72–21.24, respectively). Conclusion Adolescents from low and middle SES without schoolwork support inside or outside the family are more likely to feel indifferent toward school and education.